MOŽNOSTI IN VIVO KONFOKÁLNÍ MIKROSKOPIE NERVOVÝCH VLÁKEN ROHOVKY U DIABETIKŮ - Česká Burdová, M; Lainová Vrabcová, T; Dotřelová, D; Mahelková, G (Ceska a slovenska oftalmologie, 2017)
In vivo corneal confocal microscopy (CCM) represents a new, non-invasive, rapidly developing corneal examination technique that enables individual layers of the cornea to be displayed at the cellular level. The cornea is the translucent and at the same time the most innervated tissue of the human body. Diabetic neuropathy (DN) is a serious complication of diabetes mellitus (DM). A close correlation has been demonstrated between the development of diabetic neuropathy and the pathological changes of the corneal subbasal plexus. Currently, great attention is directed towards the possibility of using CCM to determine early DN. Interestingly, changes in nerve plexus in the cornea precede the clinical manifestations of DN. Our work aims to give a comprehensive overview of the current possibilities and trends in use of in vivo CCM in connection with DN evaluation. In vivo CCM becomes important in the search for patients at risk of developing DN, in early diagnosis of DN in pre-symptomatology, in quantifying severe DN, in monitoring and evaluating the therapeutic response to DM treatment. In addition to its diagnostic and preventive significance, it is a research tool important for understanding the pathophysiology of DM changes.Key words: confocal microscopy, cornea, small fibre neuropathy, diabetes mellitus, diabetic neuropathy.
Keywords: rohovka; Cornea; Diabetic Neuropathies; konfokální mikroskopie; Humans; lidé; Microscopy, Confocal; diabetické neuropatie